Development of a Project-Based Learning Module Grounded in Ethnoscience to Enhance Students' Scientific Literacy and Collaboration Skills - Rayis, Widuri Permata Anggarbini; Herayanti, Lovy; Prayogi, Saiful; Kurnia, Nova; Muhali , Muhali (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a Project-Based Learning (PjBL) module integrated with ethnoscience in the Pancasila Student Profile (P5) program, which focuses on strengthening students’ scientific literacy and collaboration skills. Using the 4D development model (Define, Design, Develop, Disseminate), the module was validated by experts, tested for practicality, and implemented in a rural junior secondary school in West Lombok, Indonesia. The validation results indicated high feasibility, with scores of 87.3% for the module, 88.3% for student worksheets, and 97.2% for assessment instruments. Furthermore, the practicality test reached 92.97%, categorized as highly practical. The classroom implementation of the project “The Sweetness of Science in Palm Sugar” notably increased student participation, contextual understanding of scientific concepts, and teamwork. These findings demonstrate that the developed module is both valid and practical for P5 learning, offering a culturally relevant approach to support 21st-century skills. Moreover, this study contributes by showing how ethnoscience can be systematically embedded into PjBL to improve learning quality and provides implications for adapting this model across diverse Indonesian school contexts.